2011
DOI: 10.1111/j.1442-9071.2011.02576.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cataract surgery: a population-based developing world study in the Bhaktapur district, Nepal

Abstract: Correction of refractive errors, preoperative screening of coincidental diseases, reduction in surgical complication rates and monitoring of postoperative follow-up care has to be addressed seriously in order to improve the outcome of cataract surgery to meet standards proposed by the World Health Organization. In the future, longitudinal studies need to be undertaken to provide specific information on the outcomes of cataract surgery in this community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…AMD, sequelae of retinal vein occlusion, retinal detachment and macular scar were the major causes of blindness in our study. The rate of visual impairment and blindness from vitreo-retinal disorders in our study was consistent with findings from previous studies conducted in Nepal [18-22]. A higher rate of blindness among females in our study could probably be due to the fact that males had better access to health care services than females.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…AMD, sequelae of retinal vein occlusion, retinal detachment and macular scar were the major causes of blindness in our study. The rate of visual impairment and blindness from vitreo-retinal disorders in our study was consistent with findings from previous studies conducted in Nepal [18-22]. A higher rate of blindness among females in our study could probably be due to the fact that males had better access to health care services than females.…”
Section: Discussionsupporting
confidence: 92%
“…A recent population based study conducted in the Bhaktapur district reported that vitreo-retinal diseases were the second major cause of blindness following cataract, while being the most common cause of blindness among pseudophakics [21,22]. This paper will further elaborate the findings from this population based study regarding the prevalence, types and visual impairment from vitreo-retinal disorders in this district.…”
Section: Introductionmentioning
confidence: 75%
“…Reliable visual fields were those with fixation loss, false-negative, and false-positive values of 33% or less. 911 If a visual field was unreliable, the subject then completed testing during study enrollment to achieve a reliable field. A patient was considered to have “severe” glaucoma if either eye had (1) optic nerve abnormalities consistent with glaucoma as detailed above and (2) visual field abnormalities in both hemifields and/or loss within 5 degrees of fixation in at least one hemifield in the worse eye or (3) visual acuity so severely diminished by glaucoma that HVF testing could not be performed (in this latter case, the cup-to-disc ratio was required to be 0.9 or greater).…”
Section: Methodsmentioning
confidence: 99%
“…1 It is becoming increasingly evident that pre-operative screening of co-morbidities, correction of refractive errors and post-operative follow-up care are key points in achieving the sight-restoring potential of modern cataract surgery. 21 …”
Section: Introductionmentioning
confidence: 99%